SEGMENT PERFORMANCE REPORT SEBAGAI ALAT PENILAIAN PRESTASI MANAJER PADA PT. JANUR KAWANUA INDONESIA - Go, Eric Ricardo; Mogi, Grace; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Each company has responsibility and authority sharing according to every part. For knowing how far the performance of a manager from every division according to the job and responsibility, achievement evaluation of every division is needed to be made. One method of achievement evaluation is segment performance report. The role of a manager is very important in controlling a company?s operation. By using Segment Performance Report, report lists the classification the controllable fixed costs and uncontrollable fixed costs. This research?s objective is to figure out the usage of segment performance report in evaluating manager achievement. This research is conducted in PT. Janur Kawanua Indonesia, addressed at Manembo-nembo Bitung. In this research,descriptive method (qualitative) is used for comparing the actual profit loss report and also production report that have been made by PT. Janur Kawanua Indonesia, based on the concept segment performance report. This research?s result shows the company still uses this resulted conventional-based report, production cost report and operational costs have not separated among uncontrollable costs and uncontrollable costs. With this, it can be seen the difference after controllable fixed cost and controllable costs are separated at Tepung Kelapa, as much as 417,499,394.15 IDR. And at the Kopra Division, it can be also seen the difference after controllable fixed costs and uncontrollable costs are separated, as much as 127,081,716.91 IDR.